Fabrication and Characterization of Graphene Nanoplatelets/Zinc Oxide Nanocomposites as a Military Radar Absorbing Material - Anselmo Bima Rasendriya; Andri Hardiansyah; Gita Resty Amalia; Ismail Rahmadtullah; Andi Setiono; M. Zuhnir Piliang; Hotma Renta (Indonesian Scholar Society, 2025)
Stealth aircraft have the capability to intercept radar waves. One common technique involves the use of radar-absorbing materials (RAMs). This study focused on the synthesis of advanced lightweight functional materials derived from advanced carbon and semiconductor compounds for microwave absorbing through mechanical homogenization. Graphene nanoplatelets (GNP) and Zinc Oxide (ZnO) possess excellent dielectric and magnetic loss capability due to their thermal conductivity, small particle size, large surface area, disordered structure, and lightweight nature. The GNP and ZnO were developed as advanced carbon and semiconductor nanocomposites using Planetary Ball Milling (PBM) at a ratio of 1:1. This approach aimed to improve the structure, morphology, and electromagnetic performance of the materials. A comparison between the nanocomposite materials and their precursors was conducted to clarify the advantages of using nanocomposites. FE-SEM showed the layered carbon sheets in GNP. XRD exhibited the alteration in the crystallite structure of ZnO, while FTIR spectroscopy confirmed the presence of specific functional groups. In addition, the GNP/ZnO nanocomposites showed strong microwave polarization capabilities. Notably, the GNP/ZnO nanocomposite achieved the lowest RL value compared to the precursor materials with a value of -28.21 dB at 8.45 GHz and a thickness of 3 mm in the scope of X-band range. While the through power was calculated at 99.84%. Through mechanical homogenization, a well-structured disordered crystallite layered material was fabricated for military RAMs. In the industrial sector, GNP/ZnO nanocomposites showed promising potential as a lightweight and advanced functional material for future stealth aircraft applications.